ANALISIS KEAKTIFAN SISWA MELALUI PENERAPAN MODEL TEAMS GAMESTOURNAMENTS (TGT) PADA MATERI TERMOKIMIA KELAS XI IPA 5 DI 1 SMA N 15 SEMARANG - Zaeni Zaeni; Johara Aulia; Hidayah Hidayah; Fitria Fatichatul (Universitas Muhammadiyah Semarang, 2017)
Teams Games Tournament (TGT) is one of cooperative learning models easy toimplement fpt students in the class. TGT involves students activity and role of students as peer tutor, it contains game and reinforcement. TGT used tournament of academic, quiz and individual score where every single student as a team representative competes with another team to obtain a highest score. The use of TGT in learning activity could make students more relaxed, besides it could improve responsibility, honesty and teamwork. The aim of this research is to observe and know student activity during thermochemistry lesson by usingTGT in XI IPA 5 in SMA N 15 Semarang. This research used both quantitative andqualitative method, the researcher obtained data by distributing questionnaire, conducting an interview and observing the field. Based on the research, the researcher obtained the data that students activity in XI IPA 5 by using TGT within two categories “sangat baik” and “baik”. The result showed that XI IPA 5 obtained percentage of 78% regarding to visual activities, 84% regarding to listening activities, writing activities obtained percentage of 85%, 83% regarding to mental activities, while oral activities indicator obtained percentage of 60%, those percentage werecategorized into “baik”. keywords:Teams games tournament, active,cooperative learning